Analisis Wacana Van Djik pada Kompas.com dalam Pemberitaan Staycation Karyawati Cikarang - Sagita, Faikatul Anggola; Hariyanto, Didik (Universitas Muhammadiyah Sidoarjo, 2024)
As for the critical discourse analysis is one way to analyze the discourse, both delivered orally and in writing by containing the problems being studied how the text of the news in the media membenuk a public opinion. In this study aims to analyze the discourse on van djik kompas.com in the use of diction reporting staycation Cikarang employees. News that seized the attention of the people of Indonesia for some time is one of them written by the online news portal, Kompas.com. Critical Discourse Analysis Study on Kompas news.com is considered important to know how a news text made by the mass media develops in society and understand what kind of maker of the news content. To study the meaning of the word stayction in the news aired by Kompas.com, the researcher applied Van Dijk model critical discourse analysis method in descriptive qualitative approach in analyzing news. The results of this study showed that the reporting of cases of staycation by Kompas.com wrapping the meaning of “staycation